Advanced SQL-Database for bioenergy technologies - A catalogue for bio-resources, conversion technologies, energy carriers, and supply applications - Martin Dotzauer; Kai Sven Radtke; Matthias Jordan; Daniela Thrän (Heliyon, 2024)
Bioenergy is a crucial element of the future energy system with wide range of applications in electricity, heat and transport. A major challenge for the analysis and optimisation of the bioenergy system is the degree of diversity and complexity compared to wind or solar energy. A coherent database for studying the role of bioenergy in the energy system needs to cover the different entities such as bio-resources, conversion procedures and process chains. Since there is no comprehensive data collection for bioenergy so far, we develop a SQLite database by merging several existing datasets and additional information. The resulting Bio-Energy Technology Database (BET.db) provides a consistent set of 141 feedstocks as well as energy carriers, 259 conversion technologies, and 134 energy supply concepts. The proof of concept within a bioenergy system modelling a wide range of technologies for the electricity, heat and transport sectors using the BENOPT model has been successful. By providing a one-stop-shop solution for techno-economic information about on the bioenergy nexus, this blind spot can be avoided for further investigations. The current stage of development is an intermediate prototype that will be developed into a more versatile and interactive web application later on.